Role of IgM: IgG ratio in differentiating Primary and Secondary Dengue virus infection in a Tertiary Care Hospital, A Cross Sectional Study (International Journal of Food and Nutritional Sciences, 2022)
It is reported that secondary dengue causes more severe disease in comparison with primary. Thus to differentiate the two is very crucial. Our aim is to find out cut-off values of IgM:IgG ratio for early detection of secondary dengue which could further help clinicians to prevent the complications.Methods: A cross-sectional study was conducted over a period of one year involving around 936 suspected cases of dengue. Samples were tested using commercially available capture ELISA method for IgM and IgG. Real time and nested PCR was also done to find out the prevalent serotype. IgM:IgG ratio was evaluated by using receiver operating characteristic curve analysis for the differentiation of Primary and Secondary Dengue.Results: Among the total 91 serologically confirmed dengue patients, forty-seven (51.6%) were found to be Primary and forty-four (48.4%) were secondary dengue infection with male preponderance. Using the WHO diagnostic criteria, dengue fever (DF) patients without warning signs added up to 51.6%, with warning signs 42.9% and severe dengue 5.5% of the total cases. Cut off ratio of IgM: IgG ratio=1.59 found out the best discrimination between primary from secondary infection. 40 out of 91 (44%) patients exhibited ratios of >1.59 whereas rest fifety one (56%) exhibited ratios of